Understanding the Molecular Structure of Natural Anthocyanins During Recovery with Ionic Liquids: A Combined Cosmo-Rs and Experimental Study - Romero-Figueroa, J; Quijada-Maldonado, E (Elsevier Ltd, 2024)
Anthocyanins, water-soluble vacuolar pigments found in various fruits and vegetables, exhibit vibrant red, purple, or blue hues contingent upon their pH levels. The stability of these pigments depends on pH. Due to that, conventional extraction methods use volatile organic acidic solvents in solid-liquid extractions (SLE). Despite the widespread use of such solvents, the molecular mechanisms governing the stability of anthocyanins during SLE with different solvents remain inadequately explored. This study aimed to enhance the understanding of anthocyanin stability by identifying alternative neoteric solvents, specifically hydrophilic ionic liquids (ILs). A COSMO-RS prescreening was conducted to evaluate the impact of solvent cations and anions on the anthocyanin skeleton during extraction from grape pomace. The results revealed that acetate-based ILs exhibited the highest affinity for anthocyanins. However, experimental validation demonstrated that hydrogen sulfate anion-based ILs, particularly [bmim][HSO4], yielded the most favorable outcomes, with approximately 4 mg/g of total anthocyanin equivalent at 298.15K while maintaining low pH values ensuring stability for anthocyanin molecules. Interestingly, the choice of cations within the ILs did not significantly influence the results. The main extraction mechanism is attributed to hydrogen bonding interaction. Thus, this research not only identifies an effective solvent for anthocyanin extraction but also sheds light on the crucial role of the neoteric solvent s acid characteristics in maintaining the structural integrity of these valuable pigments. © 2024 Elsevier Ltd